SETTLEMENT OF CRIMINAL CASES BY CONSULTATION IN THE CRIMINAL ACT OF THEFT IN THE FAMILY IN SEUNAGAN DISTRICT, NAGAN RAYA REGENCY - Jalaluddin, Jalaluddin; Nurila, Yurma; Pratama, Agus (Prodi Ilmu Hukum, Universitas Teuku Umar, 2025)
The resolution of minor criminal acts that occur in Indonesian society can usually be achieved through several channels, one of which is through deliberation. The concept of deliberation itself is regulated in Aceh Qanun Number 9 of 2008 concerning the Development of Customary Life and Customs. So that the formulation of the problem in this study is how effective and constraining the resolution of cases through deliberation in the crime of theft in. The purpose of this study is to determine the effectiveness and constraints in resolving cases through deliberation in the crime of theft in the family. The method used is empirical juridical with a statutory approach and a case approach.The results of the study found that deliberation in the crime of theft in the family tends to be effective to be carried out because of the issue of morality and values that are still upheld. And the constraints in resolving cases through deliberation in the family are related to personal relationships between the parties who are families who tend to be more sensitive to being accessed by third parties in their resolution, so a persuasive approach is needed.